Smart learning futures: a report from the 3rd US-China smart education conference - J. Michael Spector; SLFG (The Smart Learning Futures Group) (Smart Learning Environments, 2018)
Abstract The third day of the third US-China Smart Education Conference featured a discussion with 27 thinkers representing higher education, business and industry, vocational training, and policy making. Researchers from the fields of artificial intelligence, computer science, educational technology, neuro-science and the learning sciences from many countries actively participated and are collectively the co-authors of this report. After two short presentations on computational neuropsychology and the next generation of artificial intelligence by two of the participants (Thomas Parsons and Yang Yang respectively), the participants were divided into four groups led by Phillip Harris (AECT Director), Joseph South (ISTE Chief Learning Officer), Chee-Kit Looi (NIE Head of the Learning Sciences Lab), and Maiga Chang (School of Computing and Information Systems, Athabasca University). The groups were asked to consider the following four questions: (a) What are the 5 most promising technologies likely to transform education in the next 10 years? (b) How do/will advanced learning technologies impact the future of education? (c) What challenges do advanced learning technologies bring to education? (d) What are the new demands for education in the future of society? The groups could focus as they deemed appropriate, modifying adding questions or ignoring any question. This report is a synthesis of those discussions.